Pemanfaatan Teknologi Bergerak Sebagai Media Pembelajaran Bagi Anak Usia Dini - Saida Ulfa (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
Currently, mobile technology is experiencing rapid development that can be used by parents and educators as a learning tool, starting with the introduction of literacy and numeracy for early childhood. However, the use of this technology requires supervision, because behind the various advantages offered there are weaknesses. To support its effective use in learning environments for children, educators need to have extensive knowledge in order to be ready to make decisions about how to appropriately apply technology to meet the social, physical and cognitive needs of early childhood.